The GH-IGF-1 Axis in Circadian Rhythm - Wang, Weihao; Duan, Xiaoye; Huang, Zhengxiang; Pan, Qi; Chen, Chen; Guo, Lixin (Frontiers in Molecular Neuroscience, 2021)
Organisms have developed common behavioral and physiological adaptations to the influence of the day/night cycle. The CLOCK system forms an internal circadian rhythm in the suprachiasmatic nucleus (SCN) during light / dark input. The SCN may synchronize the growth hormone (GH) secretion rhythm with the dimming cycle through somatostatin neurons, and the change of the clock system may be related to the pulsatile release of GH. The GH - insulin-like growth factor 1 (IGF-1) axis and clock system may interact further on the metabolism through regulatory pathways in peripheral organs. We have summarized the current clinical and animal evidence on the interaction of clock systems with the GH - IGF-1 axis and discussed their effects on metabolism.